Psychophysical Evaluation of Achromatic and Chromatic Vision of Workers Chronically Exposed to Organic Solvents - Lacerda, Eliza Maria da Costa Brito (Hindawi Publishing Corporation, 2012)
The purpose of this paper was to evaluate achromatic and chromatic vision of workers chronically exposed to organic solvents through psychophysical methods. Thirty-one gas station workers (31.5 ± 8.4 years old) were evaluated. Psychophysical tests were achromatic tests (Snellen chart, spatial and temporal contrast sensitivity, and visual perimetry) and chromatic tests (Ishihara's test, color discrimination ellipses, and Farnsworth-Munsell 100 hue test—FM100). Spatial contrast sensitivities of exposed workers were lower than the control at spatial frequencies of 20 and 30 cpd whilst the temporal contrast sensitivity was preserved. Visual field losses were found in 10–30 degrees of eccentricity in the solvent exposed workers. The exposed workers group had higher error values of FM100 and wider color discrimination ellipses area compared to the controls. Workers occupationally exposed to organic solvents had abnormal visual functions, mainly color vision losses and visual field constriction.